Digital Communication Campaign on Instagram @Gigigo.Id: Oral Health Education - Wakhyuningtyas, Harini; Rahmadiva, Lelita Azaria (Universitas Syiah Kuala, 2025)
This study examines a digital communication campaign conducted by Gigigo Clinic through its Instagram account, @gigigo.id, aimed at improving public education and awareness of the importance of maintaining oral health. Using a qualitative approach and case study method, this study aims to describe the campaign strategy, evaluate the effectiveness of the educational content delivered, and identify audience engagement in the campaign. Data was collected through in-depth interviews with the social media team and clinic owners, direct observation of Instagram content, and visual documentation. Findings were analyzed using the RACE (Research, Action, Communication, Evaluation) model to identify the strategic stages in the campaign's implementation. The results of the study indicate that Instagram is used by Gigigo as an educational platform, especially in reaching the target audience aged 1835 years. Consistent, interactive, and relevant content strategies were proven effective in increasing engagement and driving behavioral changes among the audience regarding oral health. This digital campaign serves as a concrete example of structured and impactful digital communication in the context of health promotion